NARAPIDANA TINDAK PIDANA NARKOTIKA: MENYOAL PELAKSANAAN PEMBEBASAN BERSYARAT DI LEMBAGA PEMASYARAKATAN - Budi Heryanto; Fietriana Rosalina Zaenudin (Universitas Suryakancana, 2023)
One part of the prisoner development in the correctional system is parole. Narcotics crime is a complex crime because of narcotics crime, the perpetrator can also be a victim. The best guidance for prisoners is returned / integrated into society and not isolated with iron bars. Based on research conducted by the author at the Class IIB Sukabumi Correctional Institution, the number of narcotics offenders is more than one-third of the total number of prisoners. The implementation of parole for prisoners of narcotics crimes related to Government Regulation Number 99 of 2012 concerning Conditions and Procedures for the Exercise of Rights for Prisoners is considered to have been successful. But on the other hand, the implementation of this parole has several obstacles, including the existence of different rules in the issue of parole, the lack of concern of related agencies that still emphasize their respective policies, procedural policies in the process of granting parole for narcotics-related crimes Regulations that take a very long time.Keywords: drug crimes; correctional institutions; conditional discharge